PENGARUH TINGKAT KESEHATAN BANK TERHADAP CORPORATE SOCIAL RESPONSIBILITY DENGAN METODE CAMELS (Studi Empiris pada Emiten Perbankan Tahun 2018-2021) - Alifah Zulfa Husna Amalia; Agus Purwanto (Diponegoro Journal of Accounting, 2023)
This study aims to examine how the effect of bank health level using CAMELS method on the disclosure of CSR on firm value. Bank health level play a role which acts as an independent variable measured by ROA for Capital, NPL for Asset Quality, BOPO for Management, ROA for Earnings, LDR for Liquidity, and IRR for Sensitivity to market risk. CSR disclosure acts as the dependent variable measured using FSSI proxy (Financial Service Sector Index).The population consist of banking companies listed on the Indonesia Stock Exchange during 2018-2021. Samples are selected using purposive sampling method and acquired 164 companies during 4 years. Testing the sample using multiple linear regression with SPSS.The results of this study indicate that ROA and LDR has an influence on CSR disclosure. NPL has negative effect on the relationship between bank health and CSR but, for CAR, BOPO and IRR has no effect on the relationship bank health rate and CSR.